PENGARUH KUALITAS PRODUK DAN PERSONAL SELLING TERHADAP KEPUASAN KONSUMENDAY OLD CHICK PADA PT SUPER UNGGAS JAYA MEDAN - Febertina Gea; Rafida Khairani; Diny Rahmah Putri; Harto Miharjo Simanullang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2020)
This study aimed at determining and analyzing the influence of product quality and personal selling on consumers of Old Chick Day at PT Super Unggas Jaya Medan. The phenomenon of product quality was that it was lack of quality, lack of personal selling, and lack of comfort in services showed by unsatisfactory customers’ satisfaction which caused the number of consumers to decline every month as the background of this research. The research method used in this research was quantitative approach. The type of this research was quantitative descriptive and the nature of this research wass descriptive explanatory. The data collection was done by interviews and questionnaires. The analytical method used was multiple linear regression analysis. The population in this study was consumers who buy Old Chick Day at PT Super Unggas Jaya Medan. Determination of samples in this study was done by using simple random sampling, so that the sample used amounted to 109 people. The results showed that product quality and personal selling had a positive and significant effect on customers’ satisfaction at PT Super Unggas Jaya Medan. From the analysis of the factors that influenced customers’ satisfaction, it could be seen that between the two variables analyzed, the most dominant one that affected consumers’ satisfaction was a variable in product quality. This was proved by the results of the calculation of each variable (t test), where t test on product quality variable was (2,017> 1,65895) and test on personal selling variable was (2,543>1,65895). The conclusion in this study was that the service quality variable rejected H0 and accepted H1. Thus, partially product quality and personal selling had a negative and significant effect on consumers’ satisfaction of PT Sumber Unggas Jaya Medan. Simultaneously the product quality variable and personal selling variable had a positive and significant effect on consumers’ satisfaction in PT Sumber Unggas Jaya Medan